Severe Hypercalcemia as Presentation of Atypical Cystic Parathyroid Adenoma: A Case Report - Paola G. Donoso Naranjo; Macarena Naranjo Arellano; Esteban Castillo Sánchez-Heredero; Isabel Martín Garrido (Annals of Internal Medicine: Clinical Cases)
Because of their similarities with parathyroid carcinomas, atypical parathyroid adenomas constitute a challenge for pathologists. The diagnosis of this kind of parathyroid tumor also can be difficult for clinicians because of the low accuracy of imaging techniques such as scintigraphy with technetium (Tc)-99m-sestamibi or ultrasonography of the neck, severe hypercalcemia, and high serum levels of intact parathyroid hormone. We present an unusual case of hyperparathyroidism caused by an atypical cystic parathyroid adenoma with hypercalcemia and negative scintigraphy that required dialysis and presented with several postoperative complications. The clinical presentation may have indicated a parathyroid carcinoma; however, a histopathologic diagnosis was key to the diagnosis.